First clinical-morphological tendencies of the treatment ofpatients with myoma of womb with ulipristal acetate - A L Tikhomirov; V V Kazenashev; O V Zayratyants; I B Manukhin (IP Berlin A.V., 2014)
The objective. To assess the effectiveness of the selective progesterone receptor modulator ulipristal (Esmya) in presurgicaltherapy of patients with uterine myoma.Patients and methods. The examination included 23 patients with uterine myoma aged 37 to 42 years, 13 patients with uterine myoma aged 21 to 41 years who received Esmya (5 mg/day for 3 months) as a presurgical treatment, 10 patients with uterine myoma aged 33 to 48 years - control group. Removed myoma nodules underwent complex histological examination that included immunohistochemical testing with the use of monoclonal antibodies to estrogen and progesterone receptors; Кi-67; phospho-histone; Вах; Bcl-2; cleaved caspase-3; VEGF.Results. After a 3-month Esmya therapy in 13 patients, the sizes of uterine myoma decreased to correspond to 2-3 wks of gestation, the sizes of the dominant nodule were reduced on the average by 3±0,4 cm in diameter, amenorrhea developed as soon as in the first cycle (complaints of profuse menstrual bleeding stopped). No undesirable effects were noted, the women pointed out to the convenient use of the drug. A morphological examination found large sites of dystrophic changes of leiomyocytes; low-active perivascular growth areas; pseudocapsule sclerosis, single mitotic figures, and marked apoptosis. Analysis of the results of immunohistochemical examination found the following results: phospho-histone and Ki-67 - in single cells; Bax - marked induction; cleaved caspase-3 - distinct expression; VEGF - weak-to-moderate expression; expression of progesterone - 78-87%.Conclusion. As has been demonstrated a decreasing of proliferation and hypertrophy of smooth muscle cells of uterine myoma, under the influence of Esmya; while the surrounding myometrium does not change. The mechanism of the regression effect of Esmya on uterine myoma has been confirmed as a selective tissue-specific «noneffective» receptor protein conformator, inhibiting transcription of progesterone in cells of uterine myoma.